Rubro de Gastos Corrientes de la Gobernación de la Provincia de los Ríos - Vargas Moncada, Edinson Martin (2018)
The Government of the Province of Los Ríos, is an entity of character public, whose purpose is the provision of services such as conflict management, operating permits, security, to the citizens of our Province in general. The Government, as the central body, is responsible for conducting the public activities and administer state assets, the same that is a legally organized society, located in a specific territory, endowed of government and laws, which exercise sovereignty and enjoy recognition international. The theme that was addressed in this document whose title is: Item of current expenditures of the Governorate of the province of Los Ríos, it focused in the national and local context to make a critical analysis of reality that in the current moments have some public institutions of our locality and country in regard to the financial issue, this analysis started from theories cited by authors who have based their research on work activities in various public entities.